2012
DOI: 10.3390/molecules17010527
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of the (TMS)3SiH Radical-Based Reagent

Abstract: This review article focuses on the recent applications of tris(trimethylsilyl)silane as a radical-based reagent in organic chemistry. Numerous examples of the successful use of (TMS)3SiH in radical reductions, hydrosilylation and consecutive radical reactions are given. The use of (TMS)3SiH allows reactions to be carried out under mild conditions with excellent yields of products and remarkable chemo-, regio-, and stereoselectivity. The strategic role of (TMS)3SiH in polymerization is underlined with emphasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 110 publications
0
59
0
3
Order By: Relevance
“…In the literature, the TTMSS-based radicals were reported to possess outstanding reactivity and new photoinitiating systems have been proposed based on TTMSS [1925]. In the present work, the maximum polymerization rates of methacrylate-based dentin adhesive were reduced dramatically by TTMSS.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In the literature, the TTMSS-based radicals were reported to possess outstanding reactivity and new photoinitiating systems have been proposed based on TTMSS [1925]. In the present work, the maximum polymerization rates of methacrylate-based dentin adhesive were reduced dramatically by TTMSS.…”
Section: Discussionmentioning
confidence: 50%
“…It has been reported that the polymerization profiles in the presence of TTMSS for acrylate were better than that obtained in the presence of EDMAB. The profiles showed an increase of both the polymerization rates and final conversions [25]. Based on these results, TTMSS was selected as a co-initiator in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to connect with the oxygen on the epoxy group to form hydroxyl group (R-OH), which makes the C-O on the epoxy group break to proceed the epoxy ring-opening reaction [26]. The opened epoxy rings can, in turn, connect each other, and the bond can continue to grow, so that the epoxy monomers can form polymer structure through ring-opening reaction [27,28]. This reaction will be terminated by adding in terminator or hydrogen ions completely consumed only.…”
Section: Resultsmentioning
confidence: 99%
“…Silane is reported to be more efficient than an amine in FRP or free radical promoted cationic polymerization (FRPCP). 3740 For the TTMSS silyl radical, a high reactivity with addition rate constant ( k add ~ 2:2×10 7 M −1 s −1 ) to methylacrylate was noted 38 . For the EDMAB generated radical, this value was 5 × 10 5 M −1 s −1 .…”
Section: Discussionmentioning
confidence: 98%